Factors Related to the Outcome of Nursing Care for Patients with Bipolar Partial Hip Replacement Surgery at the 108 Military Central Hospital in 2024 - Minh, Nguyen Hong; Duc Thuan, Mai; Van Luong, Nguyen; Dinh Tho, Pham; Thi Thu Phuong, Pham; Minh Dat, Ngo (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Abstract: Objective: To examine the factors related to the outcome of nursing care for patients after Bipolar partial hip replacement surgery at the 108 Military Central Hospital in 2024. Methods: Cross-sectional study of 124 patients diagnosed with femoral neck fractures who underwent Bipolar partial hip replacement at the Department of Joint Surgery, 108 Military Central Hospital. To evaluate the effectiveness of nursing care based on the Harris scale, the Wong-Baker FACES Pain Rating Scale and patient satisfaction with the outcome of nursing care. To use the Chi-Square statistical test to find factors related to the outcome of patient care and rehabilitation, with a statistical significance level of p<0.05. Results: The overall nursing care outcome was good at 83.9% and poor at 16.1%. The rate of patients satisfied with the care results was 81.5%. Some factors, such as gender, place of residence, treatment time, surgical characteristics and patient satisfaction with the care consultation results, were related to the outcome of nursing care. Conclusion: gender, place of residence, treatment time, surgical characteristics and patient satisfaction were related to the outcome of nursing care for patients after Bipolar partial hip replacement surgery Keywords: Nursing care, Bipolar partial hip replacement surgery.